Analysis of the factor structure of syndromes scales of ASR (Adult Self-Report) - Lucena-Santos, Paola; Moraes, João Feliz Duarte; Oliveira, Margareth Silva (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2015)
This work aims to analyze the factorial structure of central syndromes (common to both sexes), derived from the items that comprising the syndromic scales of ASR (Adult Self Report). The sample was composed of 1144 participants (617 men and 527 women) and divided into three subsamples: (a) general population (n = 262), (b) users of alcohol and other drugs (n = 407) and (c) individuals with clinic or emotional problems (n = 475). It was obtained final solution of six factors for males and seven for females. From 99 variables analyzed 79 remained in the final solution of the central syndromes, which explains 43.23% of the variance observed. The internal consistency ranged from α = 0.70 to α = 0.86.